Effect of solvent and initial water content on (R, S)-1-phenylethanol resolution - Lee, Suan Chua; Sarmidi, Mohamad Roji (Elsevier Inc., 2006)
The enzymatic resolution of (R, S)-1-phenylethanol was carried out in various organic solvents. Two commercial immobilized lipases, such as ChiroCLEC-PC and Chirazyme L2, c.f., C3, lyo used in this study could exhibit the highest performance in isooctane. The effects of initial water content on the activity and enantioselectivity of the enzymes were also investigated. The method of direct contact pre-equilibrium, such as substrate pre-equilibrium and enzyme pre-equilibrium were used in this study. The resolution was favourable in the absence of additional water and water mimicking compound such as glycerol in the reaction system. The enantioselectivity of the enzymes was not affected by the organic solvents tested and the initial water content ranging from 0 to 0.5% (v/v). The enzymes were very selective toward the (R)-1-phenylethanol with the enantioselectivity value more than 200.